Formula Approaches for Market Access Negotiations - Joseph Francois; Will Martin (Tinbergen Institute, 2002)
Most of the large tariff reductions achieved in multilateral tradenegotiations have involved tariff-cutting formulas such as the Swissformula. However, wide variations in initial tariff rates between activeparticipants call for new approaches under the Doha Development Agenda.This paper surveys a range of formula options and examines both targetedand flexible applications of the Swiss formula that target tariff escalation andpeaks, and would allow policy makers to directly target how far they willmove towards free trade, while providing some flexibility for trading offreductions in peak tariffs against reductions in lower-tariff sectors.
Keywords: F13; F1; 330; Market access; Tariff formulas; WTO; Zoll; WTO-Recht; Markteintritt; Theorie